The Metal Artifacts from the Bronze Age Excavations at Karatas-Semayük, Turkey and their Significance in Anatolia, the Near East, and the Aegean - Bordaz, Louise A.
PhD Diss.; University Microfilms 78-18,512. Cf. Diss. Abstr. 39 (1979) 5009-A.